Cinema: memória audiovisual do mundo - Marcelo Enrique Lopez da Cunha Pereira (2005)
The word restoration goes a little beyond for the simple act to restoring. It can also be understood as a powerful tool, an important part for the compilation on archive of cultural and historical value. Directing our attention for this area, we intend to not only detach the techniques of conservation and restoration of films, as also the rescue of the memory of a society, a time, considering the film as an important historical document. Any film is important under the optics of a historical analysis, therefore all not only register images, but ideas, customs, gestures of the humanity in that period. The concepts that make of the film a historical document, the sprouting of a conservation conscience and restoration, the history of some film restoration institutes of the world and particularly for Brazil, the techniques used in the recovery of the films and, in a intimate vision are analyzed in this research, the efforts of the Belas Artes School - UFMG for safeguards her proper audiovisual memory.